Investigating impact of waste reuse on the sustainability of municipal solid waste (MSW) incineration industry using emergy approach: A case study from Sichuan province, China. (July 2018) - Wang, Yanqing; Zhang, Xiaohong; Liao, Wenjie; Wu, Jun; Yang, Xiangdong; Shui, Wei; Deng, Shihuai; Zhang, Yanzong; Lin, Lili; Xiao, Yinlong; Yu, Xiaoyu; Peng, Hong
Highlights: An integrated waste incineration system was evaluated using emergy approach. This integrated system largely depends on imported inputs to run it. Bottom ash reuse obviously enhances the performance of this integrated system. Abstract: China has become the largest generator of municipal solid waste (MSW) in the world with its rapid urbanization, population growth and raising living standard. Among diverse solid waste disposal technologies, MSW incineration has been becoming an attractive choice. In terms of systematic point, an integrated MSW incineration system should include an incineration subsystem and a bottom ash (BA) disposal subsystem. This paper employed an extend emergy assessment method with several improved indicators, which considers the emissions' impact, to evaluate the comprehensive performances of an integrated MSW incineration system. One existing incineration plant in Yibin City, Sichuan Province, China, as a case study, is evaluated using the proposed method. Three alternative scenarios (scenario A: the incineration subsystem + the BA landfill subsystem; scenario B: the incineration subsystem + the concrete paving brick production subsystem using BA as raw material; scenario C: the incineration subsystem + the non-burnt wall brick production subsystem using BA as raw material) were compared. The study results reveal that the ratio of positive output is 1.225, 2.861 and 1.230, the improved environmental loading ratio is 2.715, 2.742 and 1.533, and the improved environmental sustainability index is 0.451, 1.043 and 0.803 for scenario A, B and C respectively. Therefore, reuse of BA can enhance the sustainability level of this integrated system greatly. Comparatively, scenario B has the best comprehensive performance among the three scenarios. Finally, some targeted recommendations are put forward for decision-making.